Request to release payment against R/B 017 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to release payment against R/B 017 in order to pay the worker wages and material cost for BRACU new campus project.